2016
DOI: 10.1111/jgs.14451
|View full text |Cite
|
Sign up to set email alerts
|

Using the 4 Pillars Practice Transformation Program to Increase Pneumococcal Immunizations for Older Adults: A Cluster‐Randomized Trial

Abstract: BACKGROUND Quality improvement in primary care has focused on improving adult immunization. OBJECTIVES Test the effectiveness of a step-by step, evidence-based guide, the 4 Pillars™ Immunization Toolkit, to increase adult pneumococcal vaccination. DESIGN Randomized controlled cluster trial (RCCT) in Year 1 (6/1/2013–5/31/2014) and a pre-post study in Year 2 (6/1/2014–1/31/2015) with data analyzed in 2016. Baseline year was 6/1/2012–5/31/2013. Demographic and vaccination data were derived from de-identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Second, transference, a.k.a., bleed, of the intervention to control practices within networks likely occurred. This phenomenon is well-described in cluster trial interventions [41, 42]. Third, secular trends may have contributed; however, national HPV vaccination rates are increasing at a lower rate than in this study.…”
Section: Discussionmentioning
confidence: 52%
“…Second, transference, a.k.a., bleed, of the intervention to control practices within networks likely occurred. This phenomenon is well-described in cluster trial interventions [41, 42]. Third, secular trends may have contributed; however, national HPV vaccination rates are increasing at a lower rate than in this study.…”
Section: Discussionmentioning
confidence: 52%
“…The strengths of this study lie in the use of an intervention shown to be effective in adults 2224 and adapted for use among adolescent patients, the inclusion of five vaccines, lessons learned from the parent RCCT about ways to enhance practice engagement, and the large number of adolescents included. The participating practices were all part of a single health system using a single EMR, enabling consistency in reporting vaccine administration and subsequent vaccination data collection.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention using the Toolkit was designed to assist practices in improving uptake of influenza, pneumococcal, and tetanus‐pertussis‐diphtheria (Tdap) vaccines. Vaccination rates for each vaccine are based on those observed in the trial and improvements in rates after the intervention . To simplify modeling procedures, it was assumed that the probability of receiving each vaccine was not correlated with the probability of receiving other vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…Vaccination rates for each vaccine are based on those observed in the trial and improvements in rates after the intervention. 4 To simplify modeling procedures, it was assumed that the probability of receiving each vaccine was not correlated with the probability of receiving other vaccines. It was also assumed that the probabilities of receiving the two pneumococcal vaccines (23-valent pneumococcal polysaccharide vaccine (PPSV) and 13valent pneumococcal conjugate vaccine (PCV13)) were equal.…”
Section: Methodsmentioning
confidence: 99%